The nature of cultural contribution of a community-based homestay programme - Kayat, Kalsom (University of Aegean, 2010)
An exploratory study utilizing qualitative approach was undertaken in 2005 to better understand the cultural contribution of a community-based homestay to both the rural communities and the visitors.The particular homestay, namely the Kampung Pelegong Homestay Programme (KPHP), is located in Negeri Sembilan, Malaysia.The study finds that while living culture is the core product component, education, entertainment and enrichment are important contributions of the cultural rural tourism product of KPHP to the visitors.In addition, an important finding indicates that this particular tourism product is unique as it stresses on establishing relationship (‘Sillatul-rahim’ in Malay) between hosts and guests whereby these relationships continue for years through letters, phone conversations, and emails.The programme also increases social cohesion among the hosts and contributes to their commitment to preserve and to provide knowledge on local customs and daily routine to enhance tourist experience.